Jacqueline Risset. Scritture dell'istante - SVOLACCHIA, SARA (Biblioteca di Studi di Filologia Moderna, 2021)
"Born on 25th May 1936. Two specific desires: not to become an adult, and to write". Jacqueline Risset (1936-2014) was a translator from French (Ponge, Sollers, the Tel Quel poets) and Italian (Dante, Machiavelli, Balestrini), as well as a well-known scholar for her work on Scève, Proust and Bataille. The aim of this volume is to analyse Risset's poetic work, from the beginnings with textual writing in the experimentalism of Tel Quel, through a trajectory that, crossing Dante and Stilnovism through the translation of the Divine Comedy, led the author to the elaboration of a poetics centred on "privileged instants" that open "to the elsewhere".